The Use of Predimenol After Simple Pain Intervention in High-Risk Patients: A Case Series - Rizaldy Taslim Pinzon; Aditya Aristo Marvel Nugroho (MEDICINUS, 2025)
Effective pain management is a common challenge in clinical practice, whether it involves prescription medications or over-the-counter (OTC) nonsteroidal anti-inflammatory drugs (NSAIDs). The use of NSAIDs has been linked to various risks, including cardiovascular (CV), kidney, and gastrointestinal (GI) complications. Certain group of patients face a higher likelihood of these risks. NSAIDs consumptions have been shown to cause a modest, but steady increase in the chance of experiencing CV events and developing kidney problems. In this case series, we reported a series of inflammatory pain cases. Following simple pain intervention, we administered paracetamol and Predimenol over a 10 day period. The use of Predimenol was proven to be effective in alleviating pain without causing any notable adverse effects.